Outbreak of oral ulcers (glossitis) among the students of three central schools under Tsirang district Bhutan, 2018 - Tshewang Gyeltshen; Lham Dorji; Leki Dorj; Kuenga Choden (BMC, 2021)
Abstract Background Nutritional deficiencies are common worldwide and is most notable in low and middle income countries. In the early weeks of September 2018, oral sores mostly affecting the tongue were reported in three central schools under Tsirang district, Bhutan. A total of 204 students were affected in the three central schools. All the affected students have been assessed on the outbreak and nutritional survey was conducted in the three schools. Methods A total of 204 students who complained of different oral lesions in the affected three schools were screened by the dental surgeon for clinical assessment and administered questionnaire for nutritional assessment by the nutritionist. Twenty-one students randomly selected were sent for blood tests for micronutrient assays and complete blood count. 41 students were tested for Exfoliative cell cytology to test for fungal elements. The collected data was double entered and validated using Epi-Data version 3.1 and analysed using Stata 15 IC. The characteristics of the participants are presented as frequencies, percentages, mean and standard deviation (SD). Results Almost all the affected students in all the three schools had complaints of Burning Sensation (n = 158) followed by Pain (n = 153), Impaired Taste Sensation (n = 100) and Intolerance to Spicy Food (n = 95). Nutritional assessment analysis suggested schools not meeting the Recommended Dietary Allowance (RDA) for all components of Vitamin B complexes and Iron. Conclusion Clinical assessments and nutritional survey analysis found inadequate vitamin rich dietary intakes among all the three schools. Implementation of a strict school feeding program with a balanced diet has been suggested accordingly.